Identification of an inter-cysteine loop potentially involved in the activity of Opisthorchis viverrini-granulin-1 - Rozita Takjoo; David T. Wilson; Paramjit S. Bansal; Alex Loukas; Michael J. Smout; Norelle L. Daly (Exploration of Drug Science)
Aim: Identification of small bioactive regions in proteins and peptides can be useful information in drug design studies. The current study has shown that an inter-cysteine loop of the N-terminal domain of Opisthorchis viverrini granulin-1 (Ov-GRN-1), a granulin protein from the flatworm liver fluke Opisthorchis viverrini which has potent wound healing properties, maintains the bioactivity of the full-length protein. Methods: Peptides corresponding to the three inter-cysteine loops of the N-terminal domain were produced using synthetic chemistry, and their structures and bioactivities were analyzed using nuclear magnetic resonance (NMR) spectroscopy and cell proliferation assays, respectively. Results: As expected for such small peptides, NMR analysis indicated that the peptides were poorly structured in solution. However, a seven-residue peptide corresponding to loop 2 (GRN-L2) promoted cell proliferation, in contrast to the other fragments. Conclusions: The results from the current study suggest that GRN-L2 might be responsible, in part, for the bioactivity of Ov-GRN-1, and might be a useful lead molecule for subsequent wound healing studies.